2000
DOI: 10.1063/1.480973
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of supersaturated vapor nucleation in slit pore

Abstract: Molecular dynamics simulations of nucleation of Lennard-Jones vapor confined in a slit pore have been performed. The walls of the slit pore are structureless walls; each wall interacts with vapor molecules via Lennard-Jones 9-3 potential. The rate of nucleation in the steady state is determined by analyzing time evolution of the cluster size distribution. At the same vapor density and temperature, the nucleation rate in the slit pore is higher than in the homogeneous vapor ͓K. Yasuoka and M. Matsumoto, J. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…We first considered a binary fluid mixture of water and argon (with 11.1% mole fraction of Ar) confined to the slit nanopore (D ¼ 0.62 nm) whose two opposing walls are smooth and hydrophobic (13)(14)(15). The fluid mixture was initially equilibrated at a constant temperature (T ¼ 1000 K) and a constant lateral pressure (p xy ¼ 500 MPa) and then subjected to an instantaneous quench to T ¼ 250 K. After 30 ns equilibration, a monolayer gas clathrate was observed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first considered a binary fluid mixture of water and argon (with 11.1% mole fraction of Ar) confined to the slit nanopore (D ¼ 0.62 nm) whose two opposing walls are smooth and hydrophobic (13)(14)(15). The fluid mixture was initially equilibrated at a constant temperature (T ¼ 1000 K) and a constant lateral pressure (p xy ¼ 500 MPa) and then subjected to an instantaneous quench to T ¼ 250 K. After 30 ns equilibration, a monolayer gas clathrate was observed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TIP5P model was used for the water (42). For the smooth wall, we opted the 9-3 Lennard-Jones (LJ) potential for the water-hydrophobic wall interaction (13)(14)(15)43). The MD simulations were performed using the constant lateral pressure and constant temperature (Np xy T) ensemble.…”
Section: Methodsmentioning
confidence: 99%
“…Atomistic simulations, such as molecular dynamics and Monte Carlo simulations have provided important information on the microscopic aspects of the wetting of foreign walls by liquid and crystal [36][37][38][39]62]. Recent Monte Carlo studies revealed the importance of the line tension [36,62] in the case of unstructured walls.…”
Section: Introductionmentioning
confidence: 99%
“…Note that we do not discuss here the inverse process (nucleation of fluid droplets from the vapor in confined systems, see e.g. [42,43]), and we consider neither the structure (and possible rupture) of non-volatile confined liquid bridges [44,45], nor liquid-vapor systems confined by patterned surfaces (see e.g. [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%